On a Class of Schrödinger System Problem in Orlicz–Sobolev Spaces. (30th March 2022) - El-Houari, H.; Chadli, L. S.; Moussa, H.
Abstract : Using the mountain pass theorem, we obtain the existence of a nontrivial and nonnegative weak solution of a quasi-linear Schrödinger system driven by the ω ⋅ -Laplacian operator in Orlicz–Sobolev spaces.